A data article on E-supply chain benefits from supplier׳s perspective - Mohamed Dawood Shamout; Malek Bakheet Elayan (Data in Brief, 2018)
This data article provides numeric values about one of the most important sectors in Dubai, Dubai Central Fruit and Vegetable Market (DCM), which attracted world attention through its solid infrastructure and outstanding business environment. The dataset has been collected using a questionnaire obtained from the operational managers in the selected market, and several ethical considerations during the data collection process have been applied to assure the quality and credibility of the obtained data. A structural equation modeling (SEM) was applied using IBM SPSS AMOS. In this data article, several analysis techniques have been used. This dataset shows a positive relationship between Electronic Supply Chain Management (E-SCM) processes and Customers from supplier׳s perspective. Furthermore, the results show that the assumption of the mediation role of E-SCM benefits is not supported.